2022
DOI: 10.1371/journal.pone.0265435
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of wireless continuous monitoring of vital signs without using alarms on a general surgical ward: A mixed methods study

Abstract: Background Wireless continuous vital sign monitoring by wearable devices have recently become available for patients on general wards to promote timely detection of clinical deterioration. Many continuous monitoring systems use conventional threshold alarm settings to alert nurses in case of deviating vital signs. However, frequent false alarms often lead to alarm fatigue and inefficiencies in the workplace. The aim of this study was to determine the feasibility of continuous vital sign monitoring without the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Other aspects of patient wearability such as proper adhesion of the device should also be considered, to ensure patients and are not hindered in their daily living. Moreover, nurses express a need to extend the range of validated vital signs that can be measured by patch sensors [65 ▪ ]. It is important to consider ease of use for nurses, and wearability for patients, when considering which parameters are most important to be measured and which can be determined in derivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other aspects of patient wearability such as proper adhesion of the device should also be considered, to ensure patients and are not hindered in their daily living. Moreover, nurses express a need to extend the range of validated vital signs that can be measured by patch sensors [65 ▪ ]. It is important to consider ease of use for nurses, and wearability for patients, when considering which parameters are most important to be measured and which can be determined in derivation.…”
Section: Resultsmentioning
confidence: 99%
“…combining vital sign data or other threshold settings) but did not reach a definitive alternative [73]. Another study examined the use of a CVSM system without the use of an alarm strategy and regular trend assessments of individual trends and aggregated hourly EWS scores by every nursing shift [65 ▪ ,74]. This method showed better rates of adoption and acceptability by professionals, although maintaining long-term adherence to proactive trend assessments is still a challenge [66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were seldom wrong when indicating that a patient was becoming respiratory insufficient, but missed some cases that were less obvious. Nurses indicate that alarms are not needed when continuous data is regularly assessed [ 26 ] and might even lead to alarm fatigue [ 27 ]. However, alarms might be necessary to detect signs of deterioration that are currently missed by hospital professionals, provide decision support in case of moderate or uncertain deviations, or help to find those patients that need clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that VIKI mobile monitoring devices can be worn on the body, allowing for the measurement of physiological data such as heart rate (HR), blood oxygen levels, blood pressure (BP), respiratory rate (RR), and skin temperature (T) [8,9] . These devices not only offer great convenience in nursing work but also enhance the comfort of patient monitoring [10,11] . However, the current device requires multiple modules to collect comprehensive indicators and lacks a complete set of life monitoring devices to comprehensively measure physiological indicators.…”
Section: Introductionmentioning
confidence: 99%